2019
DOI: 10.1055/a-0820-4976
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder Pain and Disability Among Post Mastectomy Patients

Abstract: Purpose The purpose of this study was to determine shoulder pain and disability among post mastectomy patients. Methods This cross sectional study was conducted in Peshawar Pakistan from June 2017 to June 2018. A self administered questionnaire was used to collect demographic information and clinical characteristics while Shoulder Pain and Disability Index (SPADI) was used to evaluate shoulder pain and disability. Female post mastectomy patients with age between 18 to 55 years were included. Patients with co-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Also, A statistically significant difference was found between the study and control groups after application of early rehabilitation ( before discharge as well as 3 months post-operative) with p. value =0.001**. Table (4): It was apparent from this table that the study group had high significant mean practice scores as compared to the control group before discharge and this highly statistically significant difference continued 3 months post-operative. Table (5): stated that, no significant difference was existed between the study and control groups before discharge regarding pain level.…”
Section: Resultsmentioning
confidence: 80%
“…Also, A statistically significant difference was found between the study and control groups after application of early rehabilitation ( before discharge as well as 3 months post-operative) with p. value =0.001**. Table (4): It was apparent from this table that the study group had high significant mean practice scores as compared to the control group before discharge and this highly statistically significant difference continued 3 months post-operative. Table (5): stated that, no significant difference was existed between the study and control groups before discharge regarding pain level.…”
Section: Resultsmentioning
confidence: 80%
“…Adequate postoperative pain control around the shoulder after mastectomy is necessary to prevent further complications like joint movement restriction, shoulder rigidity, and functional impairment [ 15 , 16 ]. The previous study by Arsh and Ullah found that over 67% of patients who underwent breast cancer surgery experienced shoulder pain and mobility difficulties, which were associated with connective tissue fibrosis in the shoulder joint [ 3 ]. Kim et al further confirmed the presence of adhesive capsulitis, biceps tenosynovitis, and thickening of coracohumeral ligament in post-mastectomy patients with chronic shoulder pain by ultrasonography [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the pain score obtained in this study was the pain at rest, which might result differently from the pain during motion. However, a self-administered questionnaire of pain section of shoulder pain and disability index (SPADI) in the previous study by Arsh and Ullah demonstrated the similar result of pain score in each activity [ 3 ]. Third, one enrolled patient was not included in the final analysis due to loss to follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is usually a clinically diagnosed disorder based on history and physical assessment. It is a musculoskeletal condition caused by damage to the soft tissues and joint capsule of the shoulder joint and characterized by inflammation and adhesions (1) . Many etiological and referral factors cause pain in the shoulder such as local pathologies, and abdominal pathologies affecting the viscera, the diaphragm and the liver.…”
Section: Introductionmentioning
confidence: 99%